Cultural journalism in Germany, 1815-1848 a critical anthology - Franzel, Sean 1976-; Swellander, Michael (Studies in German literature, linguistics and culture, 2025)
The first critical anthology of major programmatic texts of cultural journalism from the crucial period known in Germany as the Vormärz, the time before the March Revolutions of 1848. Cultural journalism - a broad category of periodical writing encompassing criticism, reporting on the arts, popular culture, politics, and society - was one of the most dynamic fields of German intellectual activity in the nineteenth century, particularly during the crucial period in Germany's history known as the Vormärz, leading up to the March revolutions of 1848. Many of the most prominent German writers, among them Heinrich Heine, Ludwig Börne, and Goethe, were active in cultural journalism during this period of increasing nationalism and clamor for a unified, democratic Germany on one hand and absolutist repression, including censorship, on the other. This critical anthology is the first collection - in English or German - of major programmatic texts of German cultural journalism from the period. It provides complete texts or excerpts, many for the first time in English, along with critical introductions to each text by a leading scholar in German Studies or a related field. It reveals the richness and dynamism of the period's discussion of the status and function of journalism and its significance for politics, aesthetics, historiography, and philosophy. Of interest to scholars in German Studies, media and book history, and those working on the history of political journalism, the book is also well suited for undergraduate and graduate courses on European literature, history, and media studies